The art of designing embedded systems - Ganssle, Jack G.
Art of Designing Embedded Systems is apart primer and part reference, aimed at practicing embedded engineers, whether working on the code or the hardware design. Embedded systems suffer from a chaotic, ad hoc development process. This books lays out a very simple seven-step plan to get firmware development under control. There are no formal methodologies to master; the ideas are immediately useful. Most designers are unaware that code complexity grows faster than code size. This book shows a number of ways to linearize the complexity/size curve and get products out faster. Ganssle shows ways t.